The influences of user capability, internal control, and information technology on the quality of accounting information systems in conventional commercial banks - Vicky Dzaky Cahaya Putra; Purwanto (Enrichment : Journal of Management, 2023)
User capabilities are required to maximize their quality in the operation of information systems. In addition, a quality accounting information system requires reasonable internal control to minimize the risks that will arise from using an accounting information system. The research employed a quantitative survey method by distributing questionnaires to conventional commercial banks in West Java. This research used primary data for the sample of this study, as many as 73 people from 12 banks with details of the Division of Accounting and Finance. For the selection of respondents, this study used convenience sampling. The data analysis technique involved complete structural equation modeling (SEM) analysis using smartPLS. The results revealed the effects of User Capabilities on the Quality of Accounting Information Systems, Internal Control on the Quality of Accounting Information Systems, and the Influence of Information Technology on the Quality of Accounting Information Systems with a moderate effect size. Through the support of information technology, this research will become essential support for the achievement of a quality accounting information system since the banks are required to follow the direction of the times of technology-based.